Zn/S-modified Cu2O nanoparticles for applications in photocatalysis. Issue 1 (June 2021) - Yuan, S J; An, Y; Yu, C L; Zhao, J; Wang, T
Abstract: A Zn/S Co-doped Cu2 O composite photocatalyst with excellent performance is reported. Zn-Cu2 O/S composite was prepared by simple hydrothermal synthesis and impregnation method. XRD, SEM and EDS analysis showed that Cu9S5 and ZnO were formed after Zn/S Co-doping, and p-n heterojunction was formed. Zn-Cu2 O/S has good visible light sensing performance, rapid carrier transport, higher photocurrent density and 100% removal rate of methyl orange. The new ternary composite Zn-Cu2 O/S has potential application value in the treatment of toxic dye wastewater.